Spremembe etnične strukture prebivalstva v Sloveniji po letu 1991 - Josipovič, Damir (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2007)
The article deals with the problems of determining the changes of ethnic structure in Slovenia in the last between-census period. The main starting point is the comparison of the last 2002 census data with that of 1991. Rough comparison shows that the share of Slovenes has diminished, though closer analysis shows the opposite. One of the emphases of the article is on the comprehension and scrutinizing of "non-answers" phenomenon appearing in census. The contribution introduces the methods, with which we can realistically determine the ethnic structure in Slovenia. Using these methods,the more realistic share of Slovenes and other bigger ethnic groups in the population has been set.
Keywords: Slovenia; Slovenija; human migration; migracije; demografija; demography; etnična struktura; popis prebivalstva